Belgian geographers at work: the occupations of graduates in 1999 - Bernadette Mérenne; Christian Kesteloot; Isabelle Thomas (Belgeo)
This article presents the first results of a survey on the occupations of geographers, conducted by the Belgian National Committee of Geography. Among those who graduated in geography from Belgian universities between 1970 and 1998, 47% now teach in secondary or higher education, 47% are employed elsewhere, 5% do not work and are currently not looking for a job and only 1% are registered as unemployed. Recently, the proportion of people employed outside education has strongly increased. Geographical studies lead hardly ever to unemployment.